2020
DOI: 10.1108/maj-06-2019-2321
|View full text |Cite
|
Sign up to set email alerts
|

An examination of factors associated with investment in internal auditing technology

Abstract: Purpose The purpose of this study is to explore whether various organizational, internal audit function and audit committee factors are associated with internal audit investment in audit technology. Design/methodology/approach The responses from 213 public and private company chief audit executives (CAEs) from seven Anglo-culture countries are analyzed from the Common Body of Knowledge (CBOK) 2015 Global Internal Auditor Practitioner Survey on specific questions addressing internal audit use of audit technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This trend in investments of outsourced IAF as reported in this study is higher than the results reported in IIA's 2010 study that reported only 26% of respondents expecting an increase in the budget (Barr‐Pulliam, 2016). Recent empirical research for CAEs from Anglo‐culture countries also reveals 30% of respondents expecting an increase in their budgets for outsourced IAF (Garven & Scarlata, 2020).…”
mentioning
confidence: 99%
“…This trend in investments of outsourced IAF as reported in this study is higher than the results reported in IIA's 2010 study that reported only 26% of respondents expecting an increase in the budget (Barr‐Pulliam, 2016). Recent empirical research for CAEs from Anglo‐culture countries also reveals 30% of respondents expecting an increase in their budgets for outsourced IAF (Garven & Scarlata, 2020).…”
mentioning
confidence: 99%
“…Specifically, amongst them, management support contributes the most to enhance internal audit effectiveness. In this regard, also other scholars argue that top management support can be considered the foundation of the internal audit effectiveness, as it is crucial to guarantee the objectivity and independence of internal auditors (Al–Twaijry et al , 2002; Cohen and Sayag, 2010) and to invest adequate resources in internal auditing (Garven and Scarlata, 2020).…”
Section: Literature Analysismentioning
confidence: 99%
“…There is a wide call for theory development explaining the analytics adoption and implementation process (Nielsen, 2018); scholars also agree that the adoption of audit analytics in industry has not progressed as expected (Ahmi et al, 2016;Bieger, 2015;Dai, 2017;Garven and Scarlatta, 2020;Pham et al, 2021). Of the group of promising reference discipline theories applicable to the phenomenon, it seems clear that a process-theoretic approach is compelling (Dagilien_ e and Klovien_ e, 2019; Krieger et al, 2021), as the elements of the decision to adopt deploy in a process that spans an interdependent series of decision junctures and influences.…”
Section: Theoretical Trendsmentioning
confidence: 99%